SOME AREAS OF LEGISLATION IMPROVEMENT ON THE PARTICIPATION OF THE PROSECUTOR IN THE CONSIDERATION OF CASES ON BRINGING TO ADMINISTRATIVE RESPONSIBILITY IN COMMERCIAL COURTS (EUROPEAN AND ASIAN LAW REVIEW, 2023)
The article considers some features of legal regulation of participation of a prosecutor in consideration of cases on administrative offenses in arbitration courts, presents the main directions of improvement of legislation regulating the participation of a prosecutor in this area. The research methodology includes general scientific methods of cognition - materialistic and dialitic, method of analysis and synthesis, special legal method - formal-legal method. The analysis of practice and theory of participation of a prosecutor in consideration of cases on administrative offenses in arbitration courts has been carried out. It is proposed to recognize, taking into account the existing practice, the existing mechanism of participation of a prosecutor in consideration of cases on administrative offenses in arbitration courts as having shortcomings, to make advisory adjustments to the legislation.
Keywords: arbitration court; prosecutor; administrative responsibility; proceedings on cases of administrative offences; participation of the prosecutor